2009
DOI: 10.1068/b33140
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Visual Environmental Economics in the Study of Public Preference and Urban Greenspace

Abstract: This is an author produced version of a paper published in Urban greenspace has consistently been argued to be of great importance to the wellbeing, health, and daily lives of residents and users. This paper reports results from a study which combined the visualisation of public greenspace with environmental economics, and which aimed to develop a method by which realistic computer models of sites could be used within preference studies. As part of a methodology which employed contingent rating to establish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The use of visualization techniques ranges from pictograms and illustrative drawings (e.g., Brouwer and Schaafsma, 2013;Johnston et al, 2002;Morse-Jones et al, 2012;Newell and Swallow, 2012;Nguyen et al, 2013) to photorealistic pictures (e.g., Arnold et al, 2009;Grêt-Regamey et al, 2007;Rehr et al, 2014), 3D visualizations (e.g., Dijkstra et al, 2003;Laing et al, 2005Laing et al, , 2009Rid and Profeta, 2011) and virtual reality representations (e.g., Bateman et al, 2009;Bishop et al, 2009). Visualizations help to convey realistic change scenarios, reduce reliance upon response heuristics, and thereby allow underlying preferences to be more effectively measured (Bateman et al, 2009).…”
Section: Methodsmentioning
confidence: 98%
“…The use of visualization techniques ranges from pictograms and illustrative drawings (e.g., Brouwer and Schaafsma, 2013;Johnston et al, 2002;Morse-Jones et al, 2012;Newell and Swallow, 2012;Nguyen et al, 2013) to photorealistic pictures (e.g., Arnold et al, 2009;Grêt-Regamey et al, 2007;Rehr et al, 2014), 3D visualizations (e.g., Dijkstra et al, 2003;Laing et al, 2005Laing et al, , 2009Rid and Profeta, 2011) and virtual reality representations (e.g., Bateman et al, 2009;Bishop et al, 2009). Visualizations help to convey realistic change scenarios, reduce reliance upon response heuristics, and thereby allow underlying preferences to be more effectively measured (Bateman et al, 2009).…”
Section: Methodsmentioning
confidence: 98%
“…These include (but are not limited to) methods using or generating: photographic materials e.g., in participatory photographic and photo-elicitation techniques (Stedman et al 2014); video materials e.g., participant-generated videos using point-of-view (POV) cameras (Brown and Banks 2014); or computer-aided visualisations e.g., of landscape change (Laing et al 2009) or interactive maps (Collins 2011).…”
Section: Mobile and Visual Research Methodsmentioning
confidence: 99%
“…Such views are holistic representations that allow the viewer to perceive various aspects of a place in a coherent way. User studies have shown the receptiveness of visualization and interactive participatory collaborations as a way to simultaneously communicate results to the large variety of stakeholders often present in city designing or modeling meetings [126,127]. However, creating such models requires considering the relationships between many parameters and effects, spanning multiple disciplines.…”
Section: Computer Graphics For Urban Design and Planningmentioning
confidence: 99%